Undermining Moral Self-deception with the Help of Puritan Pastoral Theology. Issue 1 (May 2018) - Badgett, Jonathan P.
Modernist philosophy and psychology have pursued a variety of methods and models for understanding the universal inclination of human persons toward moral self-deception. We tend, as the Scriptures reveal and as recent empirical studies have confirmed, to think more highly of ourselves and our personal moral caliber than we ought. Whereas, Freud, Sartre, and others have offered solutions to the "paradox" of self-deception—that is, how one can be both deceiver and deceived—their solutions ultimately fall short in terms of both coherence and explanatory power. From a Christian perspective, secular frameworks are bound to falter because they do not account for humanity's status as fallen and sinful before a holy God. The gospel of Jesus Christ, on the other hand, offers means not only of understanding, but overcoming, moral self-deception. Historically, no movement of Christian spirituality has been more rigorously skeptical of the human ability to "know thyself" truly than the Puritans. This analysis of Puritan pastoral theology provides a helpful lens through which to view, and undermine, the deceitfulness of the human heart.